Plany i ustʹevʺ ri︠e︡kʺ I︠U︡zhnoĭ chasti Onezhskago ozera sostavleni︠e︡ po sʺëki︠e︡ g.g. / Korivovalʺ khimicheskoi︠u︡ tushʹi︠u︡ Kapitanʺ Popovʺ - Russia. Gidrograficheskīĭ departament (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департамент, 1881)
Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; Pulkovo meridian.; Plans and river mouths of the Southern part of Lake Onega.; Includes seven maps with a sheet coverage key.; Bukhta Derevi︠a︡nskai︠a︡ [Derevyanskaya Bay] --- Ustʹe ri︠e︡ki Voldy [Vodla River Mouth] --- Ustʹe ri︠e︡ki Chernoĭ [Chernaya River Mouth] --- Guba Uĭskai︠a︡ [Uyskaya Bay] --- Bukhta Lakhta [Lakhta or Lakhtinskaya Bay] --- Ustʹe ri︠e︡ki Andomy [Andoma River Mouth] --- Ustʹe ri︠e︡ki Vytegry [Vytegra River Mouth].; "Masshtabʺ 200 sazh. vʺ di︠u︡ĭmi︠e︡ ili 1/16800." [Scale 200 sazhens in 1 inch or 1/16800].; "Na vsi︠e︡khʺ planakhʺ glubina oznachena vʺ futakhʺ." [On all plans, depth is indicated in feet].; "No. 181" -- handwritten bottom right margin Grayscale; 1:16,800